Association of serum albumin with postoperative complication in major surgeries - Dhuware, Mahendra Kumar; Divan, Abhijeet singh; Dubey, Nitesh Kumar; Bharti, Manoj Kumar (International Surgery Journal, 2021)
Background: Nutritional assessment is essential for identifying patients who are at risk of developing complications related to significant malnutrition. Serum albumin is the most important laboratory test for the diagnosis of protein-calorie under nutrition. Methods: A COHORT of 100 patients admitted for major elective surgery in the department of general surgery, Government medical college and hospital, Ambikapur, Sarguja, Chattisgarh, India. Patients who were admitted and undergoing any major elective surgeries having age above 12 years were included. Details of cases were recorded including demographic characteristics, history and clinical examination along with BMI and serum albumin. Results: Complication rate was highest in the age group of 51-60 years (57.9%) followed by the age group of 41-50 years (53.8%). The association was found statistically significant between different level of serum albumin level and their post-operative wound complications. The highest complication rate was seen in patients with renal procedures like nephrectomy and pyelolithotomy (60.0%) but the most common type of procedure observed was bowel resection and anastomosis (38.7%). Conclusions: The correlation between the serum albumin and complication rate was statistically significant in the malignant diseases when considered separately. Low serum albumin level can be used as a marker for nutritional deficiency and TPN as nutritional supplementation in certain subset of patients may reduce postoperatively septic wound complication.